Effects and Challenges of Covid-19 Pandemic on Students Learning and Assessment Results: Case Study in a Malaysian Government School - Jaspal Kaur Naranjan Singh; Jagdave Singh Avtar Singh (2021)
The Covid-19 Pandemic has caught all educators and students of the Government Schools in Malaysia by surprise as they were forced to learn from home. The Malaysian Government has instructed all schools to be closed for face-to-face teaching and learning since March 2020. The learning then took place in students’ homes, which were not equipped for such tasks, as the technology and pedagogy was not up to par. Distance learning platforms such as Google Classroom, WhatsApp and Telegram were utilised by teachers and schools to reach their students remotely to limit the disruption of education. Students use laptops, desktop computers and mobile phones when engaging with the online learning. Most of the students are from lower-income B40 families, and had little or no resources for learning except what was offered online to them. This study has investigated the effects of online learning during the COVID-19 Pandemic on the students’ online learning during PdPR and their assessment results. Another aim of the study is to investigate the effects of socio-economic status (B40) of the students and their attendance during PdPR. Lastly, the challenges faced by the students were also determined. In order to do this research, primary data is collected from six classes in a Government High School in Selangor. Structured interviews are used as a data collection tool to determine the challenges faced by students during their PdPR sessions. The findings of the correlation analysis between student attendance and their assessment results shows a significant relationship (r = 0.8321 for History and r = 0.9263 for Malay Language). Furthermore, the results of the correlation analysis between student socio-economic status (B40) and their attendance also show a significant relationship (r = -0.8231). Through the findings of this paper, it can be concluded that the student’s learning interest online promotes higher attendance, which in turn ensures higher assessment results. A secondary finding of students belonging to the B40 group determines their assessment results is found to be interesting.